Miologia do membro torácico da paca (Cuniculus paca) - Leal, Leonardo M.; Silva, Juliana A.C.E. [UNESP]; Oliveira, Fabricio S. [UNESP]; Sasahara, Tais H.C. [UNESP]; Machado, Marcia R.F. [UNESP] (FapUNIFESP (SciELO), 2016)
The objective was to describe the forelimb muscles of paca (Cuniculus paca Linnaeus, 1766), by anatomical dissection of this region. Five adult male and female C. paca, weighing 5-10kg, from the Department of Wild Animals, FCAV-Unesp, Jaboticabal/SP, were used. The animals were fixed in formaldehyde 10% and stored in saline 30% for anatomic dissection of the muscles of shoulder, arm and forearm, identifying the origin and insertion of each muscle. The results were photodocumented and discussed based on the literature of domestic animals, rats and guinea pigs. Unless some variances in the origin and insertion of each muscle and fusion of bellies of some muscle groups, in general, the muscles of shoulder, arm and forearm of paca resemble the ones of domestic animals and other rodents.
Miology of the forelimb of paca (Cuniculus paca)
Keywords: Cuniculus paca; Muscles; Paca; Rodent; Wild